Genomic fingerprints of palaeogeographic history: The tempo and mode of rift tectonics across tropical Africa has shaped the diversification of the killifish genus Nothobranchius (Teleostei: Cyprinodontiformes) - van der Merwe, P De Wet; Cotterill, Fenton P D; Kandziora, Martha; Watters, Brian R; Nagy, Béla; Genade, Tyrone; Flügel, Tyrel J; Svendsen, David S; Bellstedt, Dirk U (Molecular phylogenetics and evolution, 2021)
This paper reports a phylogeny of the African killifishes (Genus Nothobranchius, Order Cyprinodontiformes) informed by five genetic markers (three nuclear, two mitochondrial) of 80 taxa (seven undescribed and 73 of the 92 recognized species). These short-lived annual fishes occupy seasonally wet habitats in central and eastern Africa, and their distribution coincides largely with the East African Rift System (EARS). The fossil dates of sister clades used to constrain a chronometric tree of all sampled Nothobranchius recovered the origin of the genus at ~13.27 Mya. It was followed by the radiations of six principal clades through the Neogene. An ancestral area estimation tested competing biogeographical hypotheses to constrain the ancestral origin of the genus to the Nilo-Sudan Ecoregion, which seeded a mid-Miocene dispersal event into the Coastal ecoregion, followed closely (~10 Mya) by dispersals southward across the Mozambique coastal plain into the Limpopo Ecoregion. Extending westwards across the Tanzanian plateau, a pulse of radiations through the Pliocene were associated with dispersals and fragmentation of wetlands across the Kalahari and Uganda Ecoregions. We interpret this congruence of drainage rearrangements with dispersals and cladogenic events of Nothobranchius to reflect congruent responses to recurrent uplift and rifting. The coevolution of these freshwater fishes and wetlands is attributed to ultimate control by tectonics, as the EARS extended southwards during the Neogene. Geobiological consilience of the combined evidence supports a tectonic hypothesis for the evolution of Nothobranchius.
Keywords: Mitochondria; Cell Nucleus; fylogeneze; Biogeography; Sequence Analysis, DNA; Phylogeny; Fish molecular systematics; sekvenční analýza DNA; Afrika; respirační komplex IV; buněčné jádro; Phylogeography; glykosyltransferasy; Nothobranchius; Cyprinodontidae; Electron Transport Complex IV; genom; Animals; Africa; zvířata; Killifishes; African tectonics; fylogeografie; DNA; Glycosyltransferases; Genome; mitochondrie; Cyprinodontiformes